2020
DOI: 10.1105/tpc.20.00132
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Crassulacean Acid Metabolism Modes Provide Environment-Specific Water-Saving Benefits in a Leaf Metabolic Model

Abstract: Stoichiometric modelling of leaf metabolism reveals metabolic and morphological determinants for introducing Crassulacean acid metabolism and alternative watersaving flux modes into a C3 leaf in different environments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 66 publications
(70 reference statements)
3
61
0
Order By: Relevance
“…By varying the CO 2 exchange in the light period, as a proxy for stomatal conductance, our model predicted a C 3 -CAM continuum with gradual metabolic changes along the continuum ( Figure 3 ). A recent modeling study demonstrated that CAM could be a result of a trade-off between water saving and leaf productivity ( Töpfer et al, 2020 ), which is in line with our results that CAM could emerge under an evolutionary pressure for reduced light period stomatal conductance such as water saving. The key metabolic changes along the C 3 -CAM continuum included the processes in the starch/sugar-malate cycle, the TCA cycle at night, and the chloroplastic and mitochondrial ETCs, which are consistent with what we know about metabolic fluxes in CAM ( Silvera et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…By varying the CO 2 exchange in the light period, as a proxy for stomatal conductance, our model predicted a C 3 -CAM continuum with gradual metabolic changes along the continuum ( Figure 3 ). A recent modeling study demonstrated that CAM could be a result of a trade-off between water saving and leaf productivity ( Töpfer et al, 2020 ), which is in line with our results that CAM could emerge under an evolutionary pressure for reduced light period stomatal conductance such as water saving. The key metabolic changes along the C 3 -CAM continuum included the processes in the starch/sugar-malate cycle, the TCA cycle at night, and the chloroplastic and mitochondrial ETCs, which are consistent with what we know about metabolic fluxes in CAM ( Silvera et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our recent work, we focussed on studying the tradeoff between water-saving and leaf productivity and the analysis of alternative CAM-like flux modes in a C3 metabolic network [ 36 ]. In contrast with C4 photosynthesis, in CAM photosynthesis initial and re-fixation of CO 2 are not spatially but temporally separated between day and night.…”
Section: Abiotic Interactionsmentioning
confidence: 99%
“…Environment-coupled flux-balance models of leaf metabolism are a versatile means for multi-omics data integration and interpretation [ 17 , 60 ], they have closed gaps in our understanding of plant metabolism and led to the suggestion of engineering strategies to enhance plant's performance [ 36 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…As most metabolomics experiments capture data of whole tissues, our knowledge is largely biased toward prevailing cells such as mesophyll cells in leaves [118] and endosperm in seeds [119,120]. However, several works highlight the striking differences in cell-specific metabolism and the impact that less recurrent cell types have in regulating and integrating crucial physiological processes, including transpiration and photosynthesis [121,122]. Moreover, assessing metabolic heterogeneity across cells belonging to a tissue has the potential to unravel unforeseen details masked by averaging such populations of cells, thereby contributing to a deeper understanding of metabolic regulation [6].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%